Development of spray pyrolysis-synthesised Bi2O3 thin films for photocatalytic applications - Sydorenko, Jekaterina; Krunks, Malle; Katerski, Atanas; Grzibovskis, Raitis; Vembris, Aivars; Mere, Arvo; Spalatu, Nicolae; Acik, Ilona Oja (Royal Society of Chemistry, 2024)
Photocatalysis is a green and cost-effective approach to environmental remediation. While TiO2 is considered one of the benchmark photocatalysts, alternative materials such as Bi2O3 have recently attracted increasing scientific attention as prospective visible light photocatalysts. This study aimed to develop a strategy for Bi2O3 thin film deposition via ultrasonic spray pyrolysis and systematically study process variables for the deposition of β-Bi2O3 thin films for photocatalytic applications. To achieve the aim, the precursor solution concentration as well as deposition and annealing temperature were optimised. The structural, optical, morphological, chemical and wettability properties of the obtained Bi2O3 thin films were investigated with respect to the effect on the photocatalytic oxidation of 10 ppm methyl orange (MO). The highest photocatalytic activity (48% in 5 h) under UV-A was recorded for the β-Bi2O3 film deposited using 0.1 M precursor solution at 300 °C and heat-treated for 1 h in air at 350 °C. Deposition at 300 °C resulted in an amorphous film structure, whereas annealing at 350 °C led to the formation of the β-Bi2O3 phase with the dominant facet orientation (220). These results show the suitability of spray pyrolysis for the deposition of Bi2O3 thin films with promising results for MO dye degradation, expanding the range of suitable photocatalytic materials. © 2024 The Royal Society of Chemistry. --//-- This is an open-access article Sydorenko, Jekaterina and Krunks, Malle and Katerski, Atanas and Grzibovskis, Raitis and Vembris, Aivars and Mere, Arvo and Spalatu, Nicolae and Acik, Ilona Oja, "Development of spray pyrolysis-synthesised Bi2O3 thin films for photocatalytic applications", RSC Adv., 2024, volume 14, issue 28, http://dx.doi.org/10.1039/D4RA02907K published under the CC BY-NC licence.
This research was funded by the Estonian Ministry of Education and Research, Estonian Research Council project PRG627, European Union's Horizon 2020 programme under the ERA Chair project 5GSOLAR, grant agreement No. 952509 and the Estonian Centre of Excellence project TK210; TK210U8. The authors acknowledge Valdek Mikli for SEM measurements.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics